Draft Annual Plan 2003-2004 (Sectoral Plans) Volume-III Government of Nagaland - Planning Commission (Planning Commission, 2003)
The Department of Science & Technology in the state has its areas of activities aimed at promotion and development of new and relevant technologies and act as a coordination department for all technical and scientific inputs to maximize benefit for the overall development of the state. The activities of the department broadly covers the following areas I) S & T popularization II) Research & Development projects on both S & T sector and Ecology & Environment III) Viable projects on Non-conventional Sources of Energy and IV) Promotion and development of Information Technology (IT) activities which will include creation of IT infrastructure in the State and V) Biotechnology projects.
Government of Nagaland, Planning and Co-ordination Department